Perceptions and experiences of commercial virtual reality games in early postoperative rehabilitation among cardiac surgical patients: A qualitative study - Zhongkang Wu; Xihan Li; Lin Li; Yan Zhang; Xiao Shen (Digital Health)
Background Although numerous studies have focused on the outcomes of virtual reality games for early rehabilitation in postoperative cardiac surgical patients, research on these patients’ perceptions and experiences with virtual reality games has been limited. Objectives The aim of this qualitative study was to provide insights into the perceptions and experiences of postoperative cardiac surgery patients in using commercial virtual reality games during early rehabilitation. Methods A cohort of postoperative cardiac surgery patients ( n  = 12) who used the same VR games during the early rehabilitation period at the cardiac surgery intensive care unit (ICU) of a tertiary hospital in Nanjing, China, was enrolled in this study, conducted between January 2023 and December 2023. Data were collected through individual in-depth interviews and analyzed using Colaizzi's phenomenological method. Results Two themes emerged from the interviews: (1) the benefits of virtual reality games for rehabilitation, including (i) enhancing enthusiasm for rehabilitation, (ii) helping patients to focus attention, (iii) increasing individual exercise, (iv) providing enjoyment, and (v) regulating negative emotions; (2) shortcomings in the use of virtual reality games, including (i) producing stress, (ii) insufficient operating space, (iii) discomfort while wearing, (iv) difficulty in mastering the application, and (v) individualized needs. Conclusion Cardiac patients believed that the use of commercial virtual reality games during early postoperative rehabilitation was beneficial to rehabilitation, but they highlighted some shortcomings that require improvement. The results of this study provide a certain theoretical basis for the further promotion and application of commercial virtual reality games in clinical practice in the future.